Pengujian Filter Fisik (Slow Sand Filter) Untuk Menurunkan Kadar Pestisida Golongan Organoklorin - Siska Rasiska; Aditya Bintan Pratama; Fitri Widiantini (Soilrens, 2017)
Organochlorine pesticide is one of the pesticide that has high persistency and toxic. One of the attempt to degrade organochlorine pesticide using cheaper and easier way is using the slow sand filter technology. The research aimed to test the slow sand filter and to obtain the best filter media combination for degrading organochlorine pesticide. The experiment was conducted at the Laboratory of Pesticide and Toxicology, Laboratory of Plant Protection Biotechnology and Laboratory of Chemical and Soil Fertility, Faculty of Agriculutre, Padjadjaran Univeristy from December 2016 – May 2017. The experimental design used the observative and descriptive design with 8 treatments and repeated twice. P1 (activated carbon and gravel), P2 (sand and gravel), P3 (silica sand and gravel), P4 (activated carbon and zeolite), P5 (sand and zeolite), P6 (silica sand and zeolite), P7 (activated carbon, silica sand and zeolite), P8 (activated carbon, sand and gravel). The result showed that all treatments of slow sand filter were able to degrade organochlorine pesticide and the best filter media combination was from P7 with ability to degrade the pesticide level by 82,86%.Key words: slow sand filter, activated carbon, silica sand, sand, gravel, zeolite